Les leçons de l’incorporation de l’expertise hydrogéomorphologique dans la doctrine française de prévention des risques d’inondation - David Goutx (VertigO)
Although the general principles of the flood prevention policy in France seem to be broadly accepted, the performance of the systems in place is often disappointing. We put forward the hypothesis that this operational inefficiency is partially explained by the presence, amidst a robust and uncontested flood prevention policy, of unmovable areas of potential conceptual debates unconsciously hidden. Any innovative idea must be buttressed by a broad enough expertise to validate its compatibility with the existing doctrine whilst assuring technical compatibility with it. The analyse of what happened in the case of hydrogeomorphology, shows the success of a strategy used to facilitate the incorporation of a naturalist technical method into a body of doctrine solidly anchored in an culture of science and engineering but also inhibiting any potential theoretical developments which could have, trough discourse, given impetus to the development of the theoretical aspects of natural disaster prevention in France. Paradoxically, the felicitous conditions at the emergence of hydrogeomorphology are not present anymore despite the increased volume of reflexion generated by the application of the Directive 2007/60/EC of the European Parliament and of the Council of 23 October 2007 on the assessment and management of flood risks.